2014
DOI: 10.1016/j.joca.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cartilage damage in femoroacetabular impingement with standardized dGEMRIC at 3 T

Abstract: Standardized dGEMRIC at 3 T is accurate in detecting cartilage damage and could improve preoperative assessment in femoroacetabular impingement (FAI). As cartilage lesions in FAI are localized, visual inspection of the Standardized dGEMRIC maps is more accurate than an average z for the acetabular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…They demonstrated that visual inspection of the standardized dGEMRIC maps was more accurate than an average z for the acetabular cartilage [70]. Others proposed to normalize regional T1 Gd values by dividing them by the average T1 Gd of the total (acetabular and femoral) cartilage, to draw attention to areas of abnormalities [25].…”
Section: Pearls and Pitfallsmentioning
confidence: 99%
“…They demonstrated that visual inspection of the standardized dGEMRIC maps was more accurate than an average z for the acetabular cartilage [70]. Others proposed to normalize regional T1 Gd values by dividing them by the average T1 Gd of the total (acetabular and femoral) cartilage, to draw attention to areas of abnormalities [25].…”
Section: Pearls and Pitfallsmentioning
confidence: 99%
“…This can be measured using MRI [2][3][4]6]. Lattanzi et al [24] reported accuracy of 58%, sensitivity of 52%, and specificity of 67% in detecting cartilage damage in femoroacetabular impingement using dGEMRIC.…”
Section: Introductionmentioning
confidence: 99%
“…Another disadvantage of the technique is the lack of specificity for the concentration of GAG molecules in the cartilage, although the examination time has been reduced considerably. Newer studies point to an advantage of the combination of T2 mapping and dGEMRIC, which combines high sensitivity and specificity [16,17].…”
Section: Functional Cartilage Imagingmentioning
confidence: 99%